2016
DOI: 10.1371/journal.pone.0164053
|View full text |Cite
|
Sign up to set email alerts
|

Production, Quality Control, Stability and Pharmacotoxicity of a Malaria Vaccine Comprising Three Highly Similar PfAMA1 Protein Molecules to Overcome Antigenic Variation

Abstract: Plasmodium falciparum apical membrane antigen 1 (PfAMA1) is a leading asexual blood stage vaccine candidate for malaria. In preparation for clinical trials, three Diversity Covering (DiCo) PfAMA1 ectodomain proteins, designed to overcome the intrinsic polymorphism that is present in PfAMA1, were produced under Good Manufacturing Practice (GMP) in Pichia pastoris. Using identical methodology, the 3 strains were cultivated in 70-L scale fed-batch fermentations and PfAMA1-DiCos were purified by two chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(62 reference statements)
0
4
0
1
Order By: Relevance
“…Although AMA-1 is the major target in naturally-acquired invasion inhibitory antibodies, this protein has a high degree of allelic diversity 56 , 57 ; several studies analyzing AMA-1 sequences from different geographical regions have shown that the ama-1 gene is under balancing selection, thereby posing a challenge when designing a vaccine based on this antigen 58 61 . Even though different authors have suggested including multiple alleles in a vaccine to induce antibodies having wide-scale reactivity and thus covering the parasite population’s global genetic diversity 62 , 63 , it is also important to ascertain which AMA-1 regions are involved in this protein’s vital functions to guide any immune response towards these regions thereby leading to developing control methods covering Plasmodium ’s broad allele spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Although AMA-1 is the major target in naturally-acquired invasion inhibitory antibodies, this protein has a high degree of allelic diversity 56 , 57 ; several studies analyzing AMA-1 sequences from different geographical regions have shown that the ama-1 gene is under balancing selection, thereby posing a challenge when designing a vaccine based on this antigen 58 61 . Even though different authors have suggested including multiple alleles in a vaccine to induce antibodies having wide-scale reactivity and thus covering the parasite population’s global genetic diversity 62 , 63 , it is also important to ascertain which AMA-1 regions are involved in this protein’s vital functions to guide any immune response towards these regions thereby leading to developing control methods covering Plasmodium ’s broad allele spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The field of malaria vaccines has historically seen many candidate antigens from all lifecycle stages produced for clinical trial as recombinant proteins in bacterial- and yeast-based expression platforms including E. coli , 41 47 Lactococcus lactis , 48 Saccharomyces cerevisiae 49 , 50 and Pichia pastoris . 51 54 However, generation of full-length PfRH5 protein proved particularly problematic in these heterologous expression platforms. Consequently, viral-vectored immunization led to the first promising results in animal models, 15 whereby antigen is expressed in situ from virally infected muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of antibodies against recombinant PfAMA1 and PfCSP, as well as those against two conserved synthetic PfCSP peptides, were measured by in-house optimized ELISAs. The recombinant PfAMA1 antigen (amino acids 25 – 545) was based on the 3D7 parasite clone antigen (NCBI Reference Sequence: NC_037282), expressed in Pichia pastoris and purified by a methodology that has been previously described ( Faber et al., 2008 ; Faber et al., 2016 ). The recombinant PfCSP antigen (amino acids 26 – 383) contained 4 NVDP and 38 NANP repeats (NCBI Reference Sequence: XM_001351086.1) from the 3D7 clone and was expressed in Lactococcus lactis as previously described ( Singh et al., 2018 ; Singh et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%